Predicting the change in the coronary calcium score in patients with diabetes. (25th November 2020) - Bellinge, J; Lee, S.C; Francis, R; Phillips, M; Schultz, C
Abstract: Background: The rate of increase of coronary arterial calcification score (CCS) on serial CT-scans years apart is a potent marker of cardiovascular risk but identifies risk only after irreversible damage has occurred. Molecular imaging may assist in identifying patients who are at risk of developing severe arterial calcification. Purpose: To determine if 18F-Sodium Fluoride Positron Emission Tomography (18F-NaF PET) can predict and anatomically locate the progression of CCS over 2 years. Methods: Subjects with diabetes mellitus underwent a baseline 18F-NaF PET scan and a CT CCS. The CT CCS was repeated after 2 years. 18F-NaF PET tracer uptake was measured as the maximum tissue to background ratio (TBRmax) and using a pre-defined cut-off for positivity, arteries were dichotomised into 18F-NaF positive and negative. We compared the change in the CCS between coronary arteries that were positive and negative for 18F-NaF uptake. Results: In forty-one participants (mean age 65.0±7.1, male: 63.4%) a total of 163 coronary arteries were included in the analysis. Fifty-two (31.9%) coronary arteries were 18F-NaF positive at baseline and 111 (68.1%) were negative. After 2.8 [2.4–3.2] years follow-up, the TBRmax at baseline correlated with the time-standardised change in the CCS (Spearmans' rho 0.33, p<0.001). The time-standardised change in the CCS was higher in coronary arteries that were 18F-NaF positive compared to negative (48.9 [13.6–119.7] v 3.3 [0–27.9], p<0.001). The time-standardised change in coronary calcium score increased across patients with increasing number of 18F-NaF positive arteries at baseline (p=0.006) (Figure 1). Conclusions: 18F-NaF PET activity at baseline is associated with new co-localised calcifications 2.8 years later Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): Royal Perth Hospital Research Foundation